Pathophysiology and management of chronic inflammatory demyelinating polyneuropathy - Desai, Urvi (Henry Stewart Talks, 2026)
Chronic Inflammatory Demyelinating Polyneuropathy (CIDP), CIDP pathology, CIDP immunopathogenesis, CIDP treatment goals, Intravenous immunoglobulin (IVIG), Plasma exchange (PLEX), Corticosteroid (CSS), Subcutaneous immunoglobulin (SCIG), Neonatal Fc receptor inhibitors, Complement inhibitors